Pneumonia due to Ochrobactrum intermedium in an ICU patient - Georgios Meletis; Pinelopi Amoiridou; Paraskevi Mantzana; Ioanna Soultati; Efthymia Protonotariou; Lemonia Skoura (New Microbes and New Infections, 2024)
Ochrobactrum intermedium is recognized as a rare emerging opportunistic pathogen mostly related with bloodstream infections. In this report, we describe the first clinical case of pneumonia due to O. intermedium. The case involved a 71-year old tetraplegic man hospitalized for vertebral fractures after falling from a ladder.